LONGITUDINAL ANALYSIS OF DIABETIC CHOROIDOPATHY IN PROLIFERATIVE DIABETIC RETINOPATHY TREATED WITH PANRETINAL PHOTOCOAGULATION USING WIDEFIELD SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY. Issue 3 (March 2022) - Russell, Jonathan F.; Zhou, Hao; Shi, Yingying; Shen, Mengxi; Gregori, Giovanni; Feuer, William J.; Wang, Ruikang K.; Rosenfeld, Philip J.
Abstract : Purpose: Widefield swept-source optical coherence tomography (OCT) imaging was used to characterize choroidal thickness and vascularity at baseline in proliferative diabetic retinopathy (PDR) and longitudinally after panretinal photocoagulation (PRP). Methods: Patients with treatment-naive PDR were imaged at baseline and at 1 week, 1 month, and 3 months after PRP. Previously validated algorithms were used to calculate the mean choroidal thickness (MCT) and choroidal vascularity index (CVI) in 5 regions of 12 mm × 12 mm scans. Results: Fourteen PDR eyes were included. Baseline MCT in PDR eyes did not differ significantly from normal eyes, but CVI measurements in PDR eyes were lower in all regions ( P < 0.001–0.008). After PRP, MCT measurements in PDR eyes were significantly lower at 1 month and 3 months in all regions ( P < 0.001–0.005) except the fovea ( P = 0.074). However, CVI measurements did not change over time in any region after PRP. Conclusion: The choroid in PDR eyes has a smaller CVI than that in normal eyes. After PRP, the choroidal thickness decreases outside the fovea, but the CVI remains constant, which suggests that a relative decrease in choroidal vascularity persists. These widefield swept-source OCT results are consistent with choroidal alterations found in histopathological reports of diabetic choroidopathy. Abstract : Widefield swept-source optical coherence tomography imaging of eyes with proliferative diabetic retinopathy demonstrated that the diabetic choroid is abnormal throughout the macula. This approach can be applied to investigate choroidal dysfunction in other retinal diseases.